Spectrum of Neuroimaging Findings in Post-COVID-19 Vaccination: A Case Series and Review of Literature - Shitiz Sriwastava; Ashish K. Shrestha; Syed Hassan Khalid; Mark A. Colantonio; Divine Nwafor; Samiksha Srivastava (MDPI AG, 2021)
Background and Purpose: The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first detected in Wuhan, China in December 2019. Symptoms range from mild flu-like symptoms to more severe presentations, including pneumonia, acute respiratory distress syndrome (ARDS), and even death. In response to the COVID-19 pandemic, the Emergency Use Authorization (EUA) approved the use of several vaccines. Because vaccines have been fast-tracked for emergency use, the short and long-term safety profile has been an area of concern. The aim of this paper is to extensively review published literature regarding post-COVID-19 vaccination neurological complications and characterize neuroimaging findings from three case presentations for early diagnosis and treatment. Methods: The analysis includes data from PubMed and Google Scholar. Articles included were retrieved from database inception beginning December 2020 with no language restrictions. Terms used include "SARS-CoV-2", "post Covid vaccination", "neurological complications", "Guillain-barre Syndrome", "Transverse-myelitis", "Cerebral Venous Sinus thrombosis", and "Cerebral hemorrhage". Results: The literature review yielded several neurological complications post vaccination, including cerebral sinus venous thrombosis, transverse myelitis, Guillain-Barré Syndrome and optic neuritis, to name a few. Patient case presentation findings were consistent with documented results in published literature. Conclusions: We present a case series with a thorough literature review documenting adverse neurological affects following COVID-19 vaccination. Our case presentations and literature review highlight the importance of neuroimaging when diagnosing post-COVID-19 vaccination adverse effects. MRI imaging study is an important tool to be considered in patients presenting with post-COVID-19 vaccination-related unexplained neurological symptoms for accurate diagnosis.